Molecular cloning and sequence analysis of gdhA gene of Pasteurella multocida B:2 - S. O., Sarah; Saad, Mohd Zamri; Zakaria, Zunita; Awang Junaidi, Awang Hazmi; Saw, Po Po (Medwell Online, 2006)
Pasteurella multocida is recognized as an important pathogen of animals that causes a wide spectrum of diseases, collectively termed as pasteurellosis. The bacteria possess several housekeeping genes that maintain the viability of the bacteria. One of the housekeeping genes is the gdhA gene that serves as a major link between carbon and nitrogen metabolism. The sequence and clones of the gdhA gene of P. multocida B:2 is identified and described in this study. Two strains of P. multocida B:2, PM TB and Pm3030, isolated earlier from outbreaks of haemorrhagic septicaemia of cattle were used in the study. The full length gdhA gene of P. multocida B:2 was found to be 1180 bp, while the functional fragment of the gene was 652 bp. The 652 bp functional gdhA gene was found to be 98.7% homologous with the respective gene in the genome sequence of P. multocida used in haemorrhagic septicaemia vaccine preparation. The gene was successfully sequenced and later cloned into E. coli PCR 2.1-TOPO vector.